Deletion 20q12 is associated with histological transformation of nodal marginal zone lymphoma to diffuse large B‐cell lymphoma. Issue 3 (24th December 2019) - Qian, Lei; Soderquist, Craig; Schrank‐Hacker, April; Strauser, Honore; Dupoux, Vanessa; Tang, Chi Ngong; Smith, Jennifer R.; Sun, Ang; Majumdar, Sonali; Nguyen, Tran; Widura, Sandy; Landsburg, Daniel J.; et al.
Abstract: The genetic and molecular abnormalities underlying histological transformation (HT) of nodal marginal zone lymphoma (NMZL) to diffuse large B‐cell lymphoma (DLBCL) are not well known. While del(20q12) is commonly deleted in myelodysplastic syndrome it has not previously been associated with DLBCL. We recently described a case of DLBCL harboring del(20q12) in a patient with a history of MZL involving lymph nodes and skin. Here we report eight matched cases of transformed MZL(tMZL): six from nodal MZL (tNMZL) and two from splenic MZL (tSMZL). We found >20% del(20q12) in 4/6 tNMZL, but not in tSMZL, nor in unmatched DLBCL, MZL with increased large cells (MZL‐ILC), or MZL cases. To examine whether transformation is associated with a specific gene signature, the matched cases were analyzed for multiplexed gene expression using the Nanostring PanCancer Pathways panel. The differential gene expression signature revealed enrichment of inflammatory markers, as previously observed in MZL. Also, tMZL and de novo DLBCL were enriched for extracellular matrix proteins such as collagen and fibronectin, vascular development protein PDGFRβ, DNA repair protein RAD51, and oncogenic secrete protein Wnt11 . A subset of genes is expressed differentially in del(20q12) tMZL cases vs non‐del(20q12) tMZL cases. These results suggest a specific pathway is involved in the histological transformation of NMZL, which could serve as an indicator of aggressive clinical course in this otherwise indolent neoplasm.